CdS Nanoparticles Embedded in Al-MCM-41 as Visible Light Photocatalysts for Hydrogen Generation from Water - Sohrabnezhad, Shabnam (Asian Journal of Chemistry, 2011)
Aluminum-MCM-41 molecular sieve coupled with CdS nanoparticles (CdS/Al-MCM-41) were prepared by solid-state reaction. The photocatalysts were characterized by X-ray diffraction, diffused reflectance UV-VIS (DRUV-VIS) spectroscopic analysis, scanning electron microscopic, N2 adsorption and transmission electron microscopy. The H2 production rate from water photocatalytic decomposition under visible light irradiation (l > 400 nm) over CdS nanoparticles formed in Al-MCM-41 was much higher compared to the bulk CdS. The diffuse reflectance UV-visible spectra exhibited that the absorption edge was gradually blue shifted with decrease in CdS size due to the quantum confinement effect.